2002
DOI: 10.1111/j.1745-4549.2002.tb00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extrusion Cooking and Sodium Bicarbonate Addition on the Carbohydrate Composition of Black Bean Flours

Abstract: Extrusion cooking and chemical leavening agents such as sodium bicarbonate (NaHCO3), may induce changes in carbohydrate fractions of extruded black bean (Phaseolus vulgaris L.) flours. Bean flours at 20% moisture, with NaHCO3 added at levels from 0.0 to 2.0%, were extruded at a screw speed of 200 rpm. The temperature profile ranged from 23 to 160C. Extruded bean flours with 0.1 to 0.4% added NaHCO3 were selected for sugar analyses based on color and flavor acceptability. The major sugars determined in the bean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 22 publications
4
30
0
Order By: Relevance
“…Similar values, 589 g/kg dry matter (Berrios et al, 2002) and 678 g/kg dry matter (Berrios, Swanson, & Adeline Cheong, 1999), were reported for black bean flours. Dry pea had the highest concentration of TAC, followed by chickpea and lentil.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Similar values, 589 g/kg dry matter (Berrios et al, 2002) and 678 g/kg dry matter (Berrios, Swanson, & Adeline Cheong, 1999), were reported for black bean flours. Dry pea had the highest concentration of TAC, followed by chickpea and lentil.…”
Section: Resultssupporting
confidence: 82%
“…The observed reduction in insoluble fiber associated with extrusion cooking is in agreement with previous reports for cereal extrudates (Gualberto, Bergman, Kazemzadeh, & Weber, 1997). Berrios and Pan (2001), Berrios (2006) and Berrios et al (2002) also reported a decrease in insoluble fiber in bean extrudates. The effect of extrusion on soluble fiber concentrations appeared to be inconsistent.…”
Section: Lentilmentioning
confidence: 88%
See 2 more Smart Citations
“…Examples of recent studies demonstrating changes in the IDF and/or SDF contents in pulses or pulse fractions with specific processes include the following: dehulling (Wang, Hatcher, & Gawalko, 2008); germination (Martín-Cabrejas et al, 2003); soaking (Kutos, Golob, Kac, & Plestenjak, 2003;Martín-Cabrejas et al, 2006;Wang et al, 2008); fermentation (Granito et al, 2002;Martín-Cabrejas et al, 2004); cooking (Kutos et al, 2003;Marconi, Ruggeri, Cappelloni, Leonardi, & Carnovale, 2000;Martín-Cabrejas et al, 2006;Periago, Ros, & Casas, 1997;Wang et al, 2008); enzymatic treatment (Caprez, Arrigoni, Neukom, & Amadò, 1987); extrusion (Berrios, Camara, Torija, & Alonso, 2002;Ralet, Della Valle, & Thibault, 1993); and thermal processing (Periago et al, 1997). Research findings from some of these studies are provided below.…”
Section: Insoluble and Soluble Dietary Fibresmentioning
confidence: 91%